Efeito antimicrobiano do peptídeo LyeTx-I associado à B-ciclodextrina em biofilmes de bactérias patógenas periodontais: estudo in vitro - Edison Andres Cruz Olivo (2016)
Biofilms are involved as etiology of bacterial infections such as periodontal disease, once they difficult to control with conventional mechanic and antibiotic therapy. Biofilms cells display mechanism of resistance making them tolerant against immune response and antibiotics. Antimicrobial peptides (AMPs) are an alternative to control bacterial biofilms because their wide spectrum and low rate of bacterial resistance. Therefore, the aim of this study was to evaluate the antibacterial activity of the synthetic peptide LyeTx I (originary of the poison of a spider Lycosaerithognata), free and associated with beta-cyclodextrin (CD) against both, first and late colonizer bacteria in planktonic state and in biofilms. The mixture of LyeTx I and CDwas characterized by infrared absorption spectroscopy. Planktonic and biofilm growth curves were done to identify the kinetics of tested bacteria. Biofilms were formed on polyethylene pegs using the calgary biofilm device (CBD) of the University of Calgary. To determine whether differences in biofilm architecture and composition exist between immature biofilms to mature biofilms formed on pegs, we examined biofilms by scanning electron microscopy at 2, 5 and 10 days. Then, the minimal inhibitory concentrations (MIC) and minimal bactericidal concentration (MBC) were determined for S. mutans, S. oralis, S. sanguinis, E. corrodens, L. acidophilus, L. casei, F. nucleatum and P. intermedia. Killing kinetics assays were performed for each species at MICs to determine the kinetic of LyeTx I. Additionally, the minimal biofilm eradication concentration (MBEC) and the percent of reduction in metabolic activity were determined for young (2-day) and mature (4-day) multispecies biofilms. The band detected between 1200-1700 cm-1 regions shows a decrease of functional group C-H aliphatic stretching vibrations that may be attributed to the formation of van der Waals interactions between CD and LyeTx I, thus confirming the presence of the association compound LyeTx I/CD. The MICs of the LyeTx I and the LyeTx I /CD were found between 62.5 - 7.81 g /mL in planktonic state. S. mutans, S. oralis, S. sanguinis and E. corrodens were the most sensitive to LyeTx I and LyeTx I /CD. The antibacterial effect of LyeTx I started within the first 15 minutes and continued for 10 hours according to results of death curves on tested bacteria. The percentage reduction of metabolic activity of biofilm cells was determined using resazurin and fluorometry (ex 570 nm / of 590 nm). LyeTx I, LyeTx I/CD and chlorhexidine (control) decreased the metabolic activity of 2-day biofilm cells at 250 g/mL and there were no statistically significant difference between the treatments (p> 0.05). In contrast, any of the tested agents decreased metabolic activity of 4-day biofilm cells. Chlorhexidine was able to slightly reduce metabolic activity of mature biofilm (p<0.05). In conclusion, the LyeTx I peptide free or associated with CD possesses antibacterial effect against planktonic periodontal pathogenic bacteria and reduce the metabolic activity in young biofilm cells acting as a bacteriostatic agent for a period of 10 hours. Therefore, this study suggests that LyeTx I and LyeTx I/CD arepromising antibacterial agents for the control of 2-day biofilms, which suggest their use as coadjuvant in periodontal mechanical therapy.